Estudio de factibilidad para la creación de una empresa dedicada al diseño y desarrollo de software en la web y servicios ERP (Planificación de Recursos Empresariales) para Pymes en la provincia de Loja - Armijos Piedra, Angel Armando (2023)
The research project called "Feasibility study for the creation of a company dedicated to the design and development of web-based software and ERP (Enterprise Resource Planning) services for PYMEs in the province of Loja", was based on data collection using methods and techniques to obtain the necessary information. According to the market study, a population of 13,272 PYMEs was identified, of which it was estimated that 6,300 would use our service in the first year, leaving an unsatisfied demand of 4,650 PYMEs. For the commercialization of the service, a marketing mix strategy (4P) was used to ensure a position in the market in the future. The technical study determined an installed and utilized capacity of 96 applications per year. The company's location is in the same city where the service is offered, specifically on José María Peña Street between Tnte. Maximiliano Rodríguez and Espíritu Santo Correa, thus facilitating access for clients and personnel in charge of production and marketing activities. In the administrative study, it was defined that the company would be a limited liability company and the organizational structure was established, considering the different hierarchical levels and the manual of functions for the personnel in charge of the activities, with a total of 7 jobs. In the financial study, the monetary values of investment and financing of the project were detailed, it will be financed through an internal source (partners' capital) of $19,761.93 and another external source (financial credit) of $12,000.00, to be paid over a period of 5 years in semiannual installments with an interest rate of 12.77%, the financial evaluation yielded an NPV of $21. 916.29, an IRR of 22.94% and a CBR of $0.32 per dollar invested, the PRC is achieved in 4 years, 3 months and 28 days, the sensitivity analysis indicates that the project can withstand a 12.96% increase in costs and a 10.12% decrease in revenues, which demonstrates its feasibility. Keywords: investment project, feasibility, web applications, software.